Understanding health service quality in emergency department through the length of stay and its determinants - Hidayati, Laily; Ismail, Akhmad; admin,; Abu Bakar,; Abdullah, Khatijah Lim (Journal of the Pakistan Medical Association, 2023)
Objective: To identify and analyse the determinants of emergency department length of stay. Method: The cross-sectional study was conducted from December 20 to 31, 2017, at the Centre of Referral Hospital after approval from the ethics review committee of Dr Soetomo General Hospital, Surabaya, Indonesia, and comprised patients of either gender aged 18 years or above who visited the emergency department who required follow-up after triage, such as diagnostics or hospitalisation. Emergency department length of stay, assessment time, review and consultation, and disposition or decision were the variables noted. Data was analysed using SPSS 18. Results: Of the 172 patients, 95(57%) were men and 74(43%) were women. The largest age group was of those aged 45-59 years 61(34.4%). There were 48(27%) cases of surgery and 124(73%) of medicine. Mean emergency department length of stay was 575.94±306.402 minutes (range: 100-2215 minutes), and it was significantly associated with assessment time (p=0.001), review and consultation time (p=0.001) and disposition or decision time (p=0.002). Conclusion: The emergency department length of stay was found to be rather prolonged and needed to be improved. Keywords: Healthcare quality, Emergency department, Length of stay, Timeframe guide model of care.